Biological Clocks and Rhythms of Anger and Aggression - Hood, Suzanne; Amir, Shimon (Frontiers in Behavioral Neuroscience, 2018)
The body’s internal timekeeping system is an under-recognized but highly influential force in behaviors and emotions including anger and reactive aggression. Predictable cycles or rhythms in behavior are expressed on several different time scales such as circadian (circa diem, or approximately 24-h rhythms) and infradian (exceeding 24 h, such as monthly or seasonal cycles). The circadian timekeeping system underlying rhythmic behaviors in mammals is constituted by a network of clocks distributed throughout the brain and body, the activity of which synchronizes to a central pacemaker, or master clock. Our daily experiences with the external environment including social activity strongly influence the exact timing of this network. In the present review, we examine evidence from a number of species and propose that anger and reactive aggression interact in multiple ways with circadian clocks. Specifically, we argue that: (i) there are predictable rhythms in the expression of aggression and anger; (ii) disruptions of the normal functioning of the circadian system increase the likelihood of aggressive behaviors; and (iii) conversely, chronic expression of anger can disrupt normal rhythmic cycles of physiological activities and create conditions for pathologies such as cardiovascular disease to develop. Taken together, these observations suggest that a comprehensive perspective on anger and reactive aggression must incorporate an understanding of the role of the circadian timing system in these intense affective states.